The Best Evidence for the Prevention and Management of Lower Extremity Deep Venous Thrombosis After Gynecological Malignant Tumor Surgery: A Systematic Review and Network Meta-Analysis - Hu, Jiaqi; Geng, Yidan; Ma, Jingyi; Dong, Xuefan; Fang, Shuqin; Tian, Jianli (Frontiers in Surgery, 2022)
Background: To search and obtain the relevant evidence of prevention and management of lower extremity deep venous thrombosis (DVT) after gynecological malignant tumor operation and to summarize the relevant evidence. Methods We searched the JBI evidence summary, up to date, the national comprehensive cancer network of the United States, the guide library of the National Institute of clinical medicine of the United Kingdom, PubMed, the Chinese biomedical literature database, CNKI, Wanfang, and other relevant evidence on the prevention and management of DVT in patients with gynecological malignant tumors. It includes clinical practice guidelines, best practice information book, expert consensus, evidence summary, original research, etc. The retrieval time limit is from database establishment till August 20, 2021. Two researchers independently evaluated the literature quality, combined with professional judgment, and extracted the literature that met the standards. Results Finally, 18 literatures were included, including eight guidelines, three evidence summaries, four systematic evaluations, two expert consensuses, and one best practice information volume. A total of 26 pieces of the best evidence on the prevention and management of postoperative venous thrombosis in gynecological malignant tumors were summarized. It includes risk assessment, drug prevention, mechanical prevention, management strategy, and health education. Conclusion This study summarized the best evidence of risk, prevention, and health management of DVT in postoperative patients with gynecological malignant tumors to provide evidence-based basis for clinical nurses and to improve the nursing level.